Prevalence and Antibiogram of Microbial Agents Causing Nosocomial Urinary Tract Infection in Surgical Ward of Dhaka Medical College Hospital (Journal of Enam Medical College, 2016)
Background: Nosocomial infections pose substantial risk to patients receiving care in hospitals. In Bangladesh, this problem is aggravated by inadequate infection control due to poor hygiene, resource and structural constraints and lack of awareness regarding nosocomial infections.Objective: We carried out this study to determine the prevalence of different microorganisms from urine in surgery ward and antimicrobial susceptibility pattern against various antibiotics.Materials and Methods: This cross sectional study was carried out in Department of Microbiology, Dhaka Medical College, Dhaka over a period of 12 months from July 2011 to June 2012. A total of 52 urine specimens were collected from catheterized patients admitted in general surgery ward of Dhaka Medical College Hospital (DMCH) and incubated in blood agar, MacConkey agar media and the isolates were identified by different biochemical tests oxidase test and reaction in MIU (motility indole urease) and Simmons citrate and TSI (triple sugar iron) media. ESBL producers were detected by double-disk synergy test (DDST).Results: Bacteria were isolated from 35 specimens and Escherichia coli was the commonest isolate (23, 65.71%) followed by Pseudomonas aeruginosa 6 (17.14%), Klebsiella pneumoniae 3 (8.57%), Acinetobacter baumannii 2 (5.72%) and Proteus vulgaris 1 (2.86%) respectively. Among the isolates, 10 (28.57%) ESBL producers were detected and the highest ESBL production was observed in Escherichia coli (8, 22.85%) followed by Klebsiella pneumoniae 1 (2.86%) and Pseudomonas aeruginosa 1 (2.86%). The isolates were resistant to most of the commonly used antimicrobial agents.Conclusion: The emergence of multi-drug resistant (MDR) bacteria poses a difficult task for physicians who have limited therapeutic options. However, the high rate of nosocomial infections and multi-resistant pathogens necessitate urgent comprehensive interventions of infection control.J Enam Med Col 2016; 6(2): 75-79